The Effect of Dividend Policy, Debt Policy on Stock Returns with Free Cash Flow as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Nanjan, Hertarisa Putri Andini; Ruslim, Herman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The present study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The study utilizes financial reports from the IDX and related company websites. The study's independent variables are in the form of dividend policy and debt policy. The study's moderating variable is free cash flow. The study's dependent variable is stock return. The data utilized in this study is secondary in nature, derived from financial reports. The objective of this study is to ascertain the impact of dividend and debt policies on stock returns, and to determine the role of free cash flow in amplifying the influence of these two policies. Quantitative data analysis commences with descriptive statistical tests, which summarize research data, including minimum, maximum, mean, median, and standard deviation values. This provides an overview before assumption and hypothesis tests are conducted. The findings of the research indicate that financial policy and free cash flow exert a substantial influence on the stock performance of manufacturing companies in Indonesia.